Genome-wide analysis of cellulose synthase (CesA) and cellulose synthase-like (Csl) proteins in Cannabis sativa L - Sipahi, Hulya; Haiden, Samuel; Berkowitz, Gerald (PeerJ, 2024)
The cellulose and hemicellulose components of plant cell walls are synthesized by the cellulose synthase (CESA) and cellulose synthase-like (CSL) gene families and regulated in response to growth, development, and environmental stimuli. In this study, a total of 29 CESA/CSL family members were identified in Cannabis sativa and were grouped into seven subfamilies (CESA, CSLA, CSLB, CSLC, CSLD, CSLE and CSLG) according to phylogenetic relationships. The CESA/CESA proteins of C. sativa were closely related phylogenetically to the members of the subfamily of other species. The CESA/CSL subfamily members of C. sativa have unique gene structures. In addition, the expressions of four CESA and 10 CsCSL genes in flower, leaf, root, and stem organs of cannabis were detected using RT-qPCR. The results showed that CESA and CSL genes are expressed at varying levels in several organs. This detailed knowledge of the structural, evolutionary, and functional properties of cannabis CESA/CSL genes will provide a basis for designing advanced experiments for genetic manipulation of cell wall biogenesis to improve bast fibers and biofuel production.
Keywords: Cannabis sativa; Cell wall biosynthesis; Gene family; Gene expression